Self-insurance Against Natural Disasters : The Use of Pension Funds in Pacific Island Countries - Guo, Si (IMF Working Papers; Working Paper, 2018)
Pacific island countries are exposed to significant risks from natural disasters. As a disaster relief measure, Fiji allowed pre-retirement pension withdrawls in the wake of Cyclone Winston in 2016. Motivated by this policy action, we provide a normative analysis of the use of early pension withdrawals after disasters, by setting up a life-cycle saving model with myopic households facing large natural disaster shocks. The model demonstrates the key trade-off between building up sufficient retirement savings and ensuring the access to savings against natural disaster shocks, and sheds light on welfare implications of early pension withdrawals.